Fluid-liquation hypothesis of the origin of the native copper mineralization in volcanites of a trappean formation of the Western Volyn area - Naumko, I. M.; Fedoryshyn, Yu. I.; Batsevych, N. V. (Reports of the National Academy of Sciences of Ukraine, 2016)
The determinative role of the fluid-liquation differentiation in the formation of the native copper mineralization in basalts of the Lower Wendian trappean complexes of the Western Volyn area is proved. Since it was determined that the crystallization of plagioclase occurred at a temperature ranging from 1200 to 1135 °C, and the impregnation of native copper in the plagioclase laths was revealed, one can affirm that, at the moment of the formation of basalt series, copper existed in a melt in the form of fine drops of the ore material. They came off the silicate melt in the course of liquation in the same temperature interval with the further redistribution and the transfer into the medium of a depth high-temperature fluid and the deposition on geochemical barriers. This has composed prerequisites for the substantiation of the fluid-liquation hypothesis of the origin of the native copper mineralization.